2020
DOI: 10.3389/fpls.2020.00419
|View full text |Cite
|
Sign up to set email alerts
|

MaCDSP32 From Mulberry Enhances Resilience Post-drought by Regulating Antioxidant Activity and the Osmotic Content in Transgenic Tobacco

Abstract: Desiccation tolerance is a complex phenomenon that depends on the regulated expression of numerous genes during dehydration and subsequent rehydration. Our previous study identified a chloroplast drought-induced stress protein (MaCDSP32) in mulberry, a thioredoxin (Trx) that is upregulated under drought conditions and is likely to confer drought tolerance to transgenic plants. Mulberry (Morus spp.) is an ecologically and economically important perennial woody plant that is widely used in forest management to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…They gradually acquire growth, morphological, physiological, and biochemical characteristics that are adapted to their local soil moisture conditions, including the "drying-wetting" cycle [9]. Plants can cope with changing external moisture conditions by changing external morphology, physiology, biochemistry, and gene expression [10,11,12]. Previous studies have shown that when water supply is restored after drought stress, plants can return to a growth state close to normal irrigation conditions through compensation mechanisms [13].Drought intensity differences can lead to different compensation effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They gradually acquire growth, morphological, physiological, and biochemical characteristics that are adapted to their local soil moisture conditions, including the "drying-wetting" cycle [9]. Plants can cope with changing external moisture conditions by changing external morphology, physiology, biochemistry, and gene expression [10,11,12]. Previous studies have shown that when water supply is restored after drought stress, plants can return to a growth state close to normal irrigation conditions through compensation mechanisms [13].Drought intensity differences can lead to different compensation effects.…”
Section: Introductionmentioning
confidence: 99%
“…The rehydration recovery of Populus trichocarpa is related to the activity of AQP [18]. In addition, overexpression of mulberry macdsp32 gene in tobacco could regulate antioxidant activity and carbohydrate substances, improving the drought resistance of transgenic tobacco, and enhance its recovery ability [12]. Therefore, understanding the recovery mechanisms of different plant species after rewatering is of great signi cance in elucidating their drought resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mulberry glutamate dehydrogenase ( GDH ) can improve the protein solubility and chlorophyll content in transgenic tobacco to increase the drought tolerance of transgenic plants [ 19 ]. A chloroplast drop-induced stress protein ( MaCDSP32 ) can increase the drought tolerance of plants by regulating the activity of SOD and the concentration of proline and soluble sugar [ 20 ]. Overexpression of receptor for activated C kinase 1 (Rack1) protein in Arabidopsis decreased the drought tolerance of transgenic plants, which may play a role as a negative regulator of drought stress [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mechanisms to drought stress have been extensively studied in broad-leaved species such as Populus nigra ( Yildirim and Kaya, 2017 ), Betula platyphylla ( Li H. Y. et al, 2020 ), and Morus spp. ( Sun et al, 2020 ), but only a few studies have focused on Haloxylon ammodendron ( Long et al, 2014 ; Fan et al, 2018 ) and Haloxylon persicum ( Thayale Purayil et al, 2020 ). Therefore, it is important to understand the drought tolerance of H. ammodendron and H. persicum .…”
Section: Introductionmentioning
confidence: 99%